EFEKTIVITAS METODE SDEP (SIMULASI, DEMONSTRASI, EKSPERIMEN, PRESENTASI) PADA PRAKTIKUM INTERNET OF THINGS SISWA SMK - Taku Neno, Khatrin Juliani (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
Lack of innovation and variety of learning methods in class XI TKJ SMK N 1 makes the IoT learning process less than optimal. The classroom atmosphere during learning is less conducive, learning time is wasted a lot and learning outcomes are less effective. The average student learning outcomes in IoT practicums do not meet the KKM score ≤ 70. This is due to the learning methods used are still limited to lectures, demonstrations and practicums. This study aims to determine the significance and effectiveness of the SDEP method in internet of things practicum for SMK students. The research method used was a true experimental design in the form of a posttest only control group design. The population and samples taken were students of class XI TKJ SMK N 1 Kupang totaling 147 students. Based on the analysis results obtained a significance value of 0.000 0.05, which means that there is a significant difference between the average student learning outcomes in classes using the CDP learning method and classes using the SDEP learning method. The N-Gain score also shows 57.7%, which means that the SDEP learning method is effective enough to be used in internet of things practicum for XI TKJ students at SMK N 1 Kupang.